Buparlisib with thoracic radiotherapy and its effect on tumour hypoxia: A phase I study in patients with advanced non-small cell lung carcinoma. (May 2019) - McGowan, Daniel R.; Skwarski, Michael; Bradley, Kevin M.; Campo, Leticia; Fenwick, John D.; Gleeson, Fergus V.; Green, Marcus; Horne, Amanda; Maughan, Timothy S.; McCole, Mark G.; Mohammed, Seid; Muschel, Ruth J.; et al.
Abstract: Background: Pre-clinically, phosphoinositide 3-kinase (PI3K) inhibition radiosensitises tumours by increasing intrinsic radiosensitivity and by reducing tumour hypoxia. We assessed whether buparlisib, a class 1 PI3K inhibitor, can be safely combined with radiotherapy in patients with non-small cell lung carcinoma (NSCLC) and investigated its effect on tumour hypoxia. Methods: This was a 3 + 3 dose escalation and dose expansion phase I trial in patients with advanced NSCLC. Buparlisib dose levels were 50 mg, 80 mg and 100 mg once daily orally for 2 weeks, with palliative thoracic radiotherapy (20 Gy in 5 fractions) delivered during week 2. Tumour hypoxic volume (HV) was measured using 18 F-fluoromisonidazole positron-emission tomography–computed tomography at baseline and following 1 week of buparlisib. Results: Twenty-one patients were recruited with 9 patients evaluable for maximum tolerated dose (MTD) analysis. No dose-limiting toxicity was reported; therefore, 100 mg was declared the MTD, and 10 patients received this dose in the expansion phase. Ninety-four percent of treatment-related adverse events were ≤grade 2 with fatigue (67%), nausea (24%) and decreased appetite (19%) most common per patient. One serious adverse event (grade 3 hypoalbuminaemia) was possibly related to buparlisib. No unexpected radiotherapy toxicity was reported. Ten (67%) of 15 patients evaluable for imaging analysis were responders with 20% median reduction in HV at the MTD. Conclusion: This is the first clinical trial to combine a PI3K inhibitor with radiotherapy in NSCLC and investigate the effects of PI3K inhibition on tumour hypoxia. This combination was well tolerated and PI3K inhibition reduced hypoxia, warranting investigation into whether this novel class of radiosensitisers can improve radiotherapy outcomes. Highlights: Buparlisib, a phosphoinositide 3-kinase (PI3K) inhibitor, is safe when combined with thoracic radiotherapy. PI3K inhibition resulted in a rapid reduction in tumour hypoxia in non–small cell lung carcinoma. This study supports the development of PI3K inhibitors as novel radiosensitisers.